2020
DOI: 10.1016/j.chest.2020.08.1198
|View full text |Cite
|
Sign up to set email alerts
|

Feasbility of Informed Choices: A Decision Aid for Cystic Fibrosis Adults and Their Surrogates in Lung Transplant and Mechanical Ventilation

Abstract: In order for people with advanced Cystic Fibrosis (CF) to engage in advance care planning (ACP) about lung transplant and invasive mechanical ventilation (IMV), we designed the InformedChoices decision aid (DA) website.1 Herein, we present results of our DA feasibility study. METHODS: Adults with advanced CF (FEV1<40%), their surrogates and CF clinicians were enrolled in a multi-site study with 2 time points (T1/T2). At T1, patients completed surveys and viewed the DA with a clinician. 1 month later (T2), pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…85%–100% of patients would recommend the PDA to someone else 35,37,42 . All three studies including clinician participants found that the majority considered the PDA acceptable 35,38,39 . Patzer et al.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…85%–100% of patients would recommend the PDA to someone else 35,37,42 . All three studies including clinician participants found that the majority considered the PDA acceptable 35,38,39 . Patzer et al.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported on decisional conflict, a standardized measure of uncertainty around a decision 38,39,42 . Vandeheem et al 42 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations